A survey of mobile edge computing - Zishu LI; Renchao XIE; Li SUN; Tao HUANG (Dianxin kexue)
Mobile edge computing (MEC) technology integrates IT service environment and cloud computing technology at the edge of the network,improving the capacities of computing and storage of the edge of network,reducing network operation and service delivery delay and further enhancing the quality of experience (QoE) of users.Thus,MEC has attracted extensive attention and has been added in the 5G standard as a key technology.Firstly,the basic concept,reference architecture and technical advantages of MEC were introduced,and the current research state of MEC were summarized from three perspectives:academia,industry and standard setting.Then,the key enablers,application scenarios and specific deployment methods of MEC were introduced in detail.Finally,the existing problems of MEC,such as mobility,security and billing,as well as privacy protection,were discussed.